KUALITAS PELAYANAN CV. BILAVA TOUR SEBAGAI BIRO PERJALANAN WISATA DI PEKANBARU - Wijaya, Fanny; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to assess the service quality provided by CV. Bilava Tour to its guests and the impact of slow responses on service quality. The research method used is descriptive qualitative research with techniques for data collection, data reduction, data presentation, and conclusion drawing. The findings of this study indicate that: first, the service quality of CV. Bilava Tour has not been fully optimized in its implementation because certain indicators do not align with high-quality service, particularly the Responsiveness dimension. On the other hand, the Tangibles, Reliability, Empathy, and Assurance indicators have been well executed in providing services to guests in accordance with the company's vision, mission, and standard operating procedures (SOPs). Second, the impact of slow responses on service quality at CV. Bilava Tour includes decreased customer satisfaction, reduced customer loyalty, and potential loss of sales opportunities. Keywords: Service Quality, Slow Response